2019
DOI: 10.1039/c9nj00054b
|View full text |Cite
|
Sign up to set email alerts
|

Efficient syntheses and antimicrobial activities of new thiophene containing pyranone and quinolinone derivatives using manganese(iii) acetate: the effect of thiophene on ring closure–opening reactions

Abstract: The syntheses, spectroscopic properties, and antimicrobial activities of new pyranones and quinoline-based dihydrofurans accompanied by 3-alkenyl-substituted structures were investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 73 publications
0
8
0
Order By: Relevance
“…A study on a series of manganese(I) tricarbonyl complexes bearing bis(2-pyridinylmethyl)(2-quinolinylmethyl)amine, bis(2-quinolinylmethyl)(2-pyridinylmethyl)amine, tris(2-quinolinylmethyl)amine, and tris(2-pyridinylmethyl)amine ligands (17, Figure 3), was reported recently by Güntzel and coworkers [58] [59]. Several other manganese metal complexes have been recently tested for their antimicrobial efficacy but were not found to be active [60][61][62][63].…”
Section: Manganese Complexesmentioning
confidence: 87%
“…A study on a series of manganese(I) tricarbonyl complexes bearing bis(2-pyridinylmethyl)(2-quinolinylmethyl)amine, bis(2-quinolinylmethyl)(2-pyridinylmethyl)amine, tris(2-quinolinylmethyl)amine, and tris(2-pyridinylmethyl)amine ligands (17, Figure 3), was reported recently by Güntzel and coworkers [58] [59]. Several other manganese metal complexes have been recently tested for their antimicrobial efficacy but were not found to be active [60][61][62][63].…”
Section: Manganese Complexesmentioning
confidence: 87%
“…A synthetic approach based on Mn(III) oxidative radical cyclization of cyclic 1,3‐diketones with 1,1‐disubstituted alkenes afforded a large library of thiophene‐substituted dihydrofuran‐fused pyranones, coumarins and quinolinones, out of which only a small number of compounds have been evaluated as antibacterial agents. [ 18 ] Dihydrofuran‐fused quinolinones presented a weak to moderate antibacterial activity, with compound 3 being the most potent against B. subtilis (MIC = 125 μg/ml) and Bacillus licheniformis (MIC = 500 μg/ml).…”
Section: Antimicrobial Compounds Based On Thiophene‐substituted Heter...mentioning
confidence: 99%
“…Manganese(III) acetate [33][34][35][36][37] and Cerium(IV) ammonium nitrate [38][39][40] are the most widely used transition metal salts in this reaction. Our research group has reported the synthesis of dihydrofuran compounds by the radical cyclization of 1,3-dicarbonyl compounds with various unsaturated systems such as aromatic conjugated alkenes [41,42], dienes [43,44] and conjugated amide derivatives [45,46] mediated by Manganese(III) acetate and Cerium(IV) ammonium nitrate.…”
Section: Introductionmentioning
confidence: 99%